Does competitively distinct operation enable performance in turbulent business environment? A study on finnish SMEs - Timilsina, Binod (De Gruyter Open, 2016)
Aligning resource choice and operations decision in the value chain (input-process-output) is one of the most important functions of a firm not only to make its operations to be competitively distinct but also very important for the firm’s growth and survival. However, the role of competitively distinct operations in maintaining better performance in dynamic and changing business environment has remained unclear. Therefore, this paper examined the relationship between competitively distinct operations, high efficiency operations and operational performance (research model one). In the similar manner the relationship between turbulent business environments, operational performance and financial performance were also examined (research model two). The study was conducted considering survey responses from 61 small and medium size enterprises from Finland. Correlation test and structural path modelling was used to test and validate the proposed hypothesis and research model. The results showed that competitively distinct operation enables high efficiency operations, which influences operational performance positively and significantly. In the similar manner, operational performance influences financial performance positively and significantly. Likewise, turbulent business environment was found to have a negative impact on operational and financial performance. The research findings are found to be adequate enough to highlight the importance of aligning resource choice and operations decisions in reducing the impact of turbulent business environment on organizational performance.
Keywords: competitively distinct operations; high efficiency operations; turbulent business environment; operational performance; financial performance; fi=Tuotantotalous|en=Industrial Management|